Formation of large nanodomains in liquid solutions near the phase boundary. Issue 99 (23rd November 2016) - Kang, Xinchen; Ma, Xiaoxue; Zhang, Jianling; Xing, Xueqing; Mo, Guang; Wu, Zhonghua; Li, Zhihong; Han, Buxing
Abstract : Large nanodomains were formed in liquid solutions near the phase separation point where the size of nanodomains increased dramatically. Abstract : We discovered that large nanodomains were formed in liquid solutions near the phase boundary, and their size increased dramatically as the composition of solutions approached the phase boundary. Different mesoporous materials were synthesized using nanodomains as templates, and the pore size could be controlled simply by the composition of solutions.